Weed Control in Pinus Plantations III-Persistance of Herbicides in Soil - Soni, Prafulla (Indian Forester, 1980)
Present investigation was undertaken to determine the persistance of two herbicides a contact herbicide (Gramaxone) and a translocated herbicide (Brush killer) in soil. It is concluded on the basis of extraction, infrared spectra and thin layer chromatography that Gramaxone decomposed in soil just after spraying due to loss of pyridilium and chlorine, while Brush killer persisted in toxic form upto eight months in soil but after that it decomposed due to liberation of chlorine and depletion of ester groups. This study shows that where short term control is required Gramaxone may be used but for more effective control Brush killer is useful. However, both the herbicides leave no harmful residue in soil.